2020
DOI: 10.1002/jmrs.439
|View full text |Cite
|
Sign up to set email alerts
|

Technical considerations for positioning and placement of a transperineal ultrasound probe during prostate radiotherapy

Abstract: This technical evaluation aims to provide practice 'how to' guidelines for radiation therapists (RTs) when positioning a transperineal ultrasound (TPUS) probe during prostate radiotherapy. Recommendations and practical tips will be provided for the best practice in TPUS-guided workflow to obtain optimal ultrasound images for accurate interpretation and registration of the prostate gland. This will assist the RTs in making consistent and accurate clinical decision in an ultrasound-guided radiotherapy workflow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…During probe placement, a reduction in corpus spongiosum thickness, a shifting of the inferior corpus spongiosum towards the prostate apex and a slight reduction in the distance of the probe surface to inferior corpus spongiosum occurred with increasing pressure. These clinical observations are supported by Pang et al (2020), reporting a reduction in the effective scan path from the inferior prostate boundary to the skin when TPUS probe pressure was increased in the Clarity system [11].…”
Section: Data Collectionmentioning
confidence: 53%
See 1 more Smart Citation
“…During probe placement, a reduction in corpus spongiosum thickness, a shifting of the inferior corpus spongiosum towards the prostate apex and a slight reduction in the distance of the probe surface to inferior corpus spongiosum occurred with increasing pressure. These clinical observations are supported by Pang et al (2020), reporting a reduction in the effective scan path from the inferior prostate boundary to the skin when TPUS probe pressure was increased in the Clarity system [11].…”
Section: Data Collectionmentioning
confidence: 53%
“…[5][6][7][8] between the anal verge and prostate apex in 100 patients, and a median value of 5 cm (range: 3-7.5) in 95 patients [9]. However, clinical observations and research have demonstrated that structures, such as the perineum and penile bulb, can be shifted into higher dose regions due to anatomical compression via pressure applied by the TPUS probe [10][11][12]. Excessive dose can result in a painful, erythematous rash with moist desquamation that impedes patient quality of care [13].…”
Section: Introductionmentioning
confidence: 99%